A Web-based Distance Diagnostic and Identification System for Extension - Jiannong Xin; Timur M. Momol; Lawrence A. Halsey; Pamela D. Roberts; Howard W. Beck (EDIS)
This document is Fact sheet ABE 327, one of a series of the Department of Agricultural and Biological Engineering, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Date first printed: July 2002.